1993
DOI: 10.1128/mcb.13.2.984
|View full text |Cite
|
Sign up to set email alerts
|

Histone H2A.X gene transcription is regulated differently than transcription of other replication-linked histone genes.

Abstract: Histone H2A.X is a replication-independent histone H2A isoprotein species that is encoded by a transcript alternatively processed at the 3' end to yield two mRNAs: a 0.6-kb mRNA ending with the stem-loop structure characteristic of the mRNAs for replication-linked histone species, and a second, polyadenylated 1.6-kb mRNA ending about 1 kb further downstream (C. Mannironi, W. M. Bonner, and C. L. Hatch, Nucleic Acids Res. 17:9113-9126, 1989). Of the two, the 0.6-kb H2A.X stem-loop mRNA predominates in many cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…SLBP levels are very low outside of S phase (Whitfield et al 2000), but the polyadenylated H2AFX mRNA is stable and some will likely be synthesized in G1 and persist into S phase when SLBP levels are high (Bonner et al 1993). RNA immunoprecipitation experiments and our α-SLBP RIP-seq data suggest that SLBP binds both isoforms, as sequencing read coverage extends downstream from the HDE into the part of the 3 â€Č UTR that is present only in the long isoform (Fig.…”
Section: H2afx Mrna Contacts Slbp At Two Distinct Sitesmentioning
confidence: 75%
See 1 more Smart Citation
“…SLBP levels are very low outside of S phase (Whitfield et al 2000), but the polyadenylated H2AFX mRNA is stable and some will likely be synthesized in G1 and persist into S phase when SLBP levels are high (Bonner et al 1993). RNA immunoprecipitation experiments and our α-SLBP RIP-seq data suggest that SLBP binds both isoforms, as sequencing read coverage extends downstream from the HDE into the part of the 3 â€Č UTR that is present only in the long isoform (Fig.…”
Section: H2afx Mrna Contacts Slbp At Two Distinct Sitesmentioning
confidence: 75%
“…During S phase, a short isoform (∌0.55 kb) that ends at the histone SL predominates whereas outside of S phase, a longer 1.6-kb isoformwhich is polyadenylated and replication-independent-is the predominate isoform ( Fig. 5A; Mannironi et al 1989;Bonner et al 1993). The H2A.X protein, which is encoded by the H2AFX gene comprises ∌10% of total H2A protein in mammalian cells (West and Bonner 1980); therefore, it must be synthesized in large quantities during S phase.…”
Section: H2afx Mrna Contacts Slbp At Two Distinct Sitesmentioning
confidence: 99%
“…Thus, current transcriptional models postulate heterogeneous arrays of multi-partite proteidDNA interaction sites for individual promoters, including DNA binding activities interacting with several but not all histone genes, and factors that may interact primarily with consensus sequences present in specific histone gene subtypes (Bell et al, 1992;Breuer et al, 1993;Dalton and Wells, 1988a,b;Dailey et al, 1988;Gallinari et al, 1989;Grimes et al, 1992;Hinkley and Perry, 1992;LaBella et al, 1988LaBella et al, ,1989Lee et al, 1991;Naeve et al, 1992;Sharma et al, 1989;van Wijnen et al, 1987van Wijnen et al, , 1992bWolfe and Grimes, 1991). These models emphasize variable degrees of complexity and versatility that permit differential expression of single histone gene copies in a number of different biological contexts (e.g., Bonner et al, 1993;Collart et al, 1988Collart et al, ,1991Dalton et al, 1989;Gomez-Cuadrado et al, 1992;Graves et al, 1985;Levine et al, 1988;Winter et al, 1985). Apart from this heterogeneity in transcriptional regulation, we postulate that there also may exist a coordinating mechanism that synchronizes transcription rates of many distinct histone genes both within and across subtype-family boundaries.…”
Section: Incmentioning
confidence: 91%
“…In addition, the replacement variant H2A family member X (H2AFX) is also present. This histone gene is unique in that it contains a stem-loop and ends in a histone 39 end when cells are in S phase but ends in a poly(A) tail outside of S phase (Bonner et al 1993). In previous work, we have shown that both forms of the H2aX mRNA are indeed bound by the SLBP in mouse cells (Whitfield 1999).…”
Section: Isolation Of Messenger Ribonucleoprotein Complexes Formed Inmentioning
confidence: 96%